Performance of warm mix asphalt compacted at reduced temperature - Jalali, Venon (2016)
The generic term Warm Mix Asphalt (WMA) refers to a variety of bituminous mixtures, which are produced through specific technologies, at temperatures approximately 15°C to 70°C lower than the typical production temperature range of conventional Hot Mix Asphalt (HMA) (i.e. 135°C to 160°C). The lower production temperatures of WMA offer a sustainable and environmental-friendly alternative to HMA via reducing the fuel consumption and greenhouse gas emission. Application of asphalt involves mixing, hauling, placement and compaction. As a general rule for HMA, if, during delivery and compaction, the mixture’s temperature drops below the minimum allowable production temperature at which adequate compaction can be achieved, then significant reductions in the performance of the resultant mixture is expected. In the case of WMA, it is expected that the effects of cool compaction on the properties and performance of the mixture will be less easily described than in HMA. This is due to the complicating presence of additives, which may modify the chemical, rheological and mechanical properties of the bitumen, as well as modifying the surface energy of both bitumen and aggregate, all of which can, consequently, affect the properties and performance of the resultant WMA mixture in a complex way not directly comparable to HMA mixtures. The overall goal of this research has been to investigate the effects and implications of temperature decline on the mechanical performance of WMA mixtures, produced in two different ways, included a ‘wax/organic additive’ technology (using a Fischer-Tropsch paraffin wax) and a ‘chemical additive’ technology (using a cationic surfactant liquid), along with determining the fundamental reasons for such effects. For this purpose, a devised comprehensive matrix of laboratory tests was performed on the produced wax-modified and chemical-additive-modified binders in order to provide the mechanical and rheological characterisation of the binders as well as their surface energy properties. The associated wax-WMA and chemical-additive-WMA, also different reference HMA mixtures were fabricated via mixing at recommended and adequate temperatures (according to the standard or the additive supplier’s advice) and compacting at a declining series of temperatures using two different compaction methods (i.e. gyratory compaction and roller compaction). A devised comprehensive set of laboratory tests was then carried out to fully characterise the manufactured WMA mixtures and their counterpart reference HMA mixtures via studying and understanding the influence of reduced production temperatures on their mechanical performance characteristics, including volumetric properties, stiffness modulus, fatigue resistance, rutting potential and viscoelastic behaviour representatives (complex stiffness modulus). The binder-aggregate dry bond strength of the various binder and aggregate combinations used in the asphalt mixtures was evaluated using the surface energy calculations combining the surface energy properties of the different binders and aggregates (pure and modified). Moreover, a mechanical assessment test was performed on different coating samples of the various binder and aggregate combinations to evaluate the binder-aggregate adhesive or binder cohesive tensile strength in different mixtures. The results show that compaction at lower temperatures does not have a considerable effect on the performance of asphalt mixtures, whether they contain additives or not, unless it occurs below 100°C (i.e. 80 and 85°C), in which case, in spite of some limited negative influences on asphalt performance, overall behaviour still remains in acceptable ranges. Moreover, it seems that overall, additives increase the sensitivity of asphalt mixtures’ properties to production temperatures variations. It was also found that gyratory compactors compact asphalt mixtures to a certain density regardless of the temperature (and probably material) because they are, in effect, strain-controlled. Thus, the compaction process in a gyratory compactor is widely insensitive to temperature. Therefore gyratory compaction is not a suitable method for investigating the performance of compaction site that imposes a fixed or set vibratory stress.